Implementation of finite element program for two-dimensional plane strain analysis / Abdul Rahman Mohammad Yusuf - Mohammad Yusuf, Abdul Rahman (1992)
The Finite Element Method is a powerful tool for the approximate solution of differential equations governing different kind of physical phenomena. Its use in industry and research is extensive and indeed it could be said that without it and its handmaiden (the computer), many problems would be incapable of solution. This presentation is based on an effort to implement Finite Element program on IBM PC Micro Computer at the School of Engineering, Institut Teknologi Mara (ITM), Shah Alam, Selangor.